2021
DOI: 10.34172/apb.2022.048
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Resistance Genes of Breast Cancer Patients – An Overview

Abstract: Purpose: Cancer is the leading challenge to human health since the dawn of early Egyptian manuscripts, where they found tumour from fossils in the modernized twentieth century. Increasing rate of incidence and death from cancer in the past few years is thought provoking. Among all type of cancers, breast cancer is very common among women and diverse in character. Drug resistance is the challenging aspect for traditional chemotherapy. Methods: Data was collected from online platform without any time restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…P-glyocoprotein (P-gp), glutathione Stransferase (GST-p), and P53 are only a few examples of MDR1encoded proteins that are involved in the chemoresistance cascade (44). In fact, Chen et al, 2022 suggested the synergistic effect of 7-Ogeranylquercetin and miR-451 on undoing MDR-1 and P-gpmediated chemoresistance in breast cancer MCF-7/ADR (Adriamycin) cells (45). The major chemoresistance mechanisms of cancer cells.…”
Section: Multidrug Resistance Genementioning
confidence: 99%
“…P-glyocoprotein (P-gp), glutathione Stransferase (GST-p), and P53 are only a few examples of MDR1encoded proteins that are involved in the chemoresistance cascade (44). In fact, Chen et al, 2022 suggested the synergistic effect of 7-Ogeranylquercetin and miR-451 on undoing MDR-1 and P-gpmediated chemoresistance in breast cancer MCF-7/ADR (Adriamycin) cells (45). The major chemoresistance mechanisms of cancer cells.…”
Section: Multidrug Resistance Genementioning
confidence: 99%